Pengaruh Model Pembelajaran Direct Instruction Terhadap Hasil Belajar IPA - Biologi - Herni Yanti Telaumbanua (JURNAL GLOBAL EDUKASI, 2021)
Abstract: Based on preliminary studies it was found that student learning outcomes were still low and the learning models used were less varied. For that, it is necessary to apply the Direct Instruction (DI) learning model that can shape student knowledge and be active in learning. The purpose of this study was to determine the effect of the Direct Instruction (DI) learning model on student learning outcomes in Biology subjects. This type of research is a quantitative research with experimental methods. The study population was 132 grade VIII students. The sample of the study was 44 students of class VIII-3 as the experimental class and 40 students of class VIII-2 as the control class. The results showed that t count was 9.84 and t table was 1.66. This shows that the value of t count> t table. In conclusion, the Direct Instruction (DI) learning model has an effect on student learning outcomes. Suggestions, it is hoped that every teacher of Biology subject to apply the Direct Instruction (DI) learning model in order to improve the abilities of students, and can improve teaching and learning methods and become reference material for further researchers who are relevant to this research.Â Keyword: Direct InstructionÂ Abstrak: Berdasarkan studi pendahuluan ditemukan bahwa hasil belajar siswa masih rendah dan model pembelajaran yang digunakan kurang bervariasi. Untuk itu, perlu di terapkan model pembelajaran Pembelajaran Direct Instruction yang dapat membentuk pengetahuan siswa dan aktif dalam pembelajaran. Tujuan penelitian ini adalah untuk mengetahui pengaruh model pembelajaran Pembelajaran Direct Instruction terhadap hasil belajar siswa pada mata pelajaran Biologi. Jenis penelitian ini adalah penelitian kuantitatif dengan metode eksperimen. Populasi penelitian adalah siswa kelas VIII yang berjumlah 132. Sampel penelitian adalah siswa kelas VIII-3 berjumlah 44 orang sebagai kelas eksperimen dan siswa kelas VIII-2 berjumlah 40 sebagai kelas kontrol. Hasil penelitian diperoleh thitung sebesar 9,84 dan ttabel sebesar 1.66. Hal tersebut menunjukan bahwa nilai thitung > ttabel. Kesimpulan, model pembelajaran Pembelajaran Direct Instruction berpengaruh terhadap hasil belajar siswa. Saran, diharapkan kepada setiap guru mata pelajaran Biologi supaya menerapkan model pembelajaran Pembelajaran Direct Instruction demi meningkatkan kemampuan yang dimiliki siswa, serta dapat memperbaiki cara belajar mengajar serta menjadi bahan referensi kepada peneliti lanjutan yang relefan dengan penelitian ini.Â Kata Kunci: Direct Instruction